2016
DOI: 10.1016/j.addbeh.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test of assessment reactivity within a web-based brief alcohol intervention study for college students

Abstract: Objective Web-based brief alcohol intervention (WBI) programs have efficacy in a wide range of college students and have been widely disseminated to universities to address heavy alcohol use. In the majority of efficacy studies, web-based research assessments were conducted before the intervention. Web-based research assessments may elicit reactivity, which could inflate estimates of WBI efficacy. The current study tested whether web-based research assessments conducted in combination with a WBI had additive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…We found no evidence of assessment reactivity resulting from study interviews in persons with HIV in Uganda. This is consistent with previous findings of no difference between study and minimally assessed or control groups with the outcome of reduced drinking or risk reduction (Cherpitel et al, 2010;Fazzino et al, 2016;Magill et al, 2012) but differs from other studies that did find evidence of assessment reactivity on alcohol use Kypri et al, 2007;McCambridge & Day, 2008;Worden et al, 2008). We also found no evidence of differences in assessment reactivity by gender, contrary to previous findings (Magill et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We found no evidence of assessment reactivity resulting from study interviews in persons with HIV in Uganda. This is consistent with previous findings of no difference between study and minimally assessed or control groups with the outcome of reduced drinking or risk reduction (Cherpitel et al, 2010;Fazzino et al, 2016;Magill et al, 2012) but differs from other studies that did find evidence of assessment reactivity on alcohol use Kypri et al, 2007;McCambridge & Day, 2008;Worden et al, 2008). We also found no evidence of differences in assessment reactivity by gender, contrary to previous findings (Magill et al, 2012).…”
Section: Discussionsupporting
confidence: 88%
“…Similar pre-treatment changes in drinking were seen in alcohol-dependent women (Epstein et al, 2005), as well as in adolescent drinkers (Kaminer et al, 2008). In contrast, several randomized studies found no difference in drinking between assessed and minimally assessed study arms, for example, among college students (Fazzino et al, 2016;Magill et al, 2012) or hazardous drinkers in hospital emergency departments (Cherpitel et al, 2010;Daeppen et al, 2007).…”
mentioning
confidence: 72%
“…All measures and interventions were completed entirely via the Internet. Recent research has shown no significant reactivity effects from online assessments combined with alcohol interventions (Fazzino, Rose, & Helzer, 2016). Participants were carefully monitored at each assessment for consumption of potentially lethal amounts of alcohol (blood alcohol concentration of .35% or greater).…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…[16][17][18] SM was initially introduced as a methodological concern in treatment studies, as it appeared that measurement reactivity was affecting treatment outcomes. [14][15][16][17][18][19][20][21] Patients often report that self-monitoring helped them to reduce use and gain important insight into their behavior. 22 Substance use studies have examined assessment as an intervention (e.g., using assessments to promote behavior change) for this reasonhowever, results are mixed across the literature as to whether SM interventions produce consistent outcomes for substance users.…”
Section: Introductionmentioning
confidence: 99%